2018
DOI: 10.1007/s10518-018-0380-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based optimisation of RC frames with friction wall dampers using a low-cost optimisation method

Abstract: A bs tr ac t Friction-based dampers can be considered as one of the suitable passive control systems for seismic strengthening and rehabilitation of existing substandard structures due to their high adjustability and good energy dissipation capability. One of the main issues in the design of these systems is to obtain the magnitude of t h e ma xi mu m slip force and the distribution of slip forces along the height of the building. In this study, a practical performance-based optimisation methodology is develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…However, they have some drawbacks such as convergence to local optimal solutions, difficult implementation, high computational effort needed to calculate derivatives of the objective functions at each load step and susceptibility to numerical noise [25,26]. More recently, Nabid et al [27,28] developed a practical method for more efficient design of friction-based wall dampers and showed that the energy dissipation capacity of the dampers can be significantly increased by using a more appropriate distribution of friction forces. Altieri et al [29] also used a linear approximation method (COBYLA) for reliability-bases optimal design of nonlinear viscous dampers for enhancing the seismic performance of steel moment resisting frames.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have some drawbacks such as convergence to local optimal solutions, difficult implementation, high computational effort needed to calculate derivatives of the objective functions at each load step and susceptibility to numerical noise [25,26]. More recently, Nabid et al [27,28] developed a practical method for more efficient design of friction-based wall dampers and showed that the energy dissipation capacity of the dampers can be significantly increased by using a more appropriate distribution of friction forces. Altieri et al [29] also used a linear approximation method (COBYLA) for reliability-bases optimal design of nonlinear viscous dampers for enhancing the seismic performance of steel moment resisting frames.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, with small activation forces, the sliding interfaces will not be effective. To address this limitation, some researchers have proposed optimization algorithm to obtain an optimum activation force over the height of the buildings [23,24,25]. Also, several damping systems have been proposed to modulate the normal force of the friction damper through an external force input, termed variable friction devices [18,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of friction device have been proposed and developed, including translational motion devices, [4][5][6][7][8][9][10][11] rotational motion devices, [11][12][13] beam column joint devices, [14][15][16] and other devices. 9,17,18 The seismic response behavior of friction-damped (FD) systems has been experimentally investigated, [19][20][21] design methods and analytical studies have been reported, [22][23][24][25][26][27][28][29] and the installation of devices into actual building structures has been performed. 30,31 In addition, research on frictional devices with disc springs has been presented.…”
Section: Introductionmentioning
confidence: 99%